GAMIFIED LOCAL STORY “LIPI POLENG” ON EFL STUDENTS' LEARNING ATTITUDE DURING Covid-19 - Ni Luh Putu Ning Septyarini Putri Astawa; I Gusti Ayu Agung Istri Sari Dewi (Program Studi Pendidikan Bahasa Inggris IKIP PGRI Pontianak, 2022)
This study presents the impact of a gamified local story “Lipi Poleng” on students’ English learning attitudes during the Covid-19 period. A quasi-experimental with one- group pre-test and post-test design was applied in this research. 29 students of a public junior highschool in Tabanan-Bali were involved in this research. Both quantitative and qualitative data were collected through pre-test and post-test close-ended and open-ended questionnaires. Paired sample t-test was implemented to analyze the quantitative data, while the qualitative data were examined descriptively using Miles and Huberman’s flow model. It was found that the use of Lipi Poleng presented a significant effect on students’ learning attitudes.